2011
DOI: 10.1590/s1808-86942011000300019
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological study of patients with head and neck sarcomas

Abstract: Sarcomas are rare tumors, mainly stemming from the embryonic mesoderm, with a high grade of morbidity and mortality.Objective: To carry out a retrospective study of head and neck sarcoma cases between 1999 and 2008 in three specialized centers in the city of Fortaleza. Materials and Methods:Data collection was based on the charts of the patients in the study. For statistical analysis purposes we used the chi-square associations and the z test for proportions.Results: We found records of 36 patients, and the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
10
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 26 publications
5
10
3
Order By: Relevance
“…8,[12][13][14] Various studies have been reported, with average samples sizes. 5,12,13,[15][16][17][18][19][20][21][22] Similar to the study by Van Damme et al, 10 not all the patients were comparable with the present study because the studies mixed adult and paediatric populations. The average duration in the reviewed publications was 193.5 months.…”
Section: Discussionsupporting
confidence: 68%
“…8,[12][13][14] Various studies have been reported, with average samples sizes. 5,12,13,[15][16][17][18][19][20][21][22] Similar to the study by Van Damme et al, 10 not all the patients were comparable with the present study because the studies mixed adult and paediatric populations. The average duration in the reviewed publications was 193.5 months.…”
Section: Discussionsupporting
confidence: 68%
“…Higher prevalence of sarcomas in females was also reported by de Bree et al 15 in a study from Netherlands and Guevara-Canales et al 12 in a Peruvian study. Contrary to our findings, higher occurrence of sarcomas among males has been reported in studies from Japan, 1 Zimbabwe, 10 Brazil, 16 and Portugal. 17 It was ascertained in this study that the overall mean age for occurrence of sarcomas was 33 ± 16 years, with 74% (n = 114) of the patients being aged 40 years and 42 years in a study from Japan, and in an Iranian study, the mean age of 41 years was reported by Alishahi et al 13 In Africa, KS has been described as one of the most common malignant tumors, being prevalent in countries with higher human immunodeficiency virus/acquired immunodeficiency syndrome prevalence.…”
Section: Discussioncontrasting
confidence: 99%
“…Adebayo et al, 19 on the contrary, reported rhabdomyosarcoma to be the third most common, accounting for 10% of all sarcomas. In contrast to the above studies and our study, Chidzonga and Mahomva 10 reported prevalence of rhabdomyosarcoma to be 23.8% in a study from Zimbabwe, and Pacheco et al 16 reported prevalence of 25%. An Iranian study 13 reported rhabdomyosarcoma to be the fourth common sarcoma, accounting for 7.61%.…”
Section: Discussioncontrasting
confidence: 99%
“…The patient has been sent to a sarcoma center for choose the ideal treatment where a chemo-radiotherapy has been proposed. The international literature agrees that is difficult to establish a standard treatment for head and neck sarcoma [54,65]. The optimal treatment is complete resection [5,[65][66].…”
Section: Discussionmentioning
confidence: 99%
“…The international literature agrees that is difficult to establish a standard treatment for head and neck sarcoma [54,65]. The optimal treatment is complete resection [5,[65][66]. Postoperative adjuvant radiotherapy is indicated for patients with low-grade tumors who have close (< 1cm) or positive margins, as well as those with high-grade tumors [66][67].…”
Section: Discussionmentioning
confidence: 99%